Ammonites from offshore deposits near Bogenfels, Namibia - Klinger, Herbert Christian; McMillan, Ian K. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2007)
Pyritized ammonite nuclei and fragments were recovered by vibracore sampling from offshore deposits near Bogenfels, Namibia. Although these could only be identified at genus level, the association of Baculites and Scaphites suggest a Coniacian age for these deposits which conforms with the age of the associated foraminifera.